MID UPPER ARM CIRCUMFERENCE AS A PREDICTOR OF BIRTH WEIGHT IN TERM PREGNANCY WITH CEPHALIC PRESENTATION - , SYARIFAH FARAH FAADHILAH, dr. Risanto Siswosudarmo, Sp.OG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. In Indonesia infant mortality rate(IMR) is still high. Based on SKDI 2007, in 1990 the number of fetal death is 68 per 100 live birth. The relationship between maternal malnutrition and consequent low birth weight babies and the perinatal morbidity and mortality is now an accepted fact. Reports from developed and developing countries show that maternal anthropometric measurement ase associated with birth outcome. Mid Upper Arm Circumference (MUAC) has already been used generally to identified malnutrition in children of developing country , especially in Indonesia it is used for screening pregnant women who has risk to delivered low birth weight baby. Objective. Determine the correlation of maternal anthropometry measuremets (MUAC) and Low Birth Weight. Method. A cross sectional study was performed in hospitals in Yogyakarta city in central java of Indonesia. A hundreds participant were recruited for this study. Result. Finding showed that the MUAC has low correlation with birth weight (r = 0.33) but shows significant correlation to birth weight satistically (p = 0.12), although still lower than fundal height. Conclusion. MUAC could be considered as predictive factors of birth weight after fundal height.